Comparative and Practical Aspects of Localization‐Based Super‐Resolution Imaging. Issue 1 (1st January 2013) - Laevsky, Gary S.; O'Connell, Christopher B.
Abstract: Super‐resolution microscopy overcomes diffraction to generate images with superior resolution compared to conventional light microscopy. Localization‐based super‐resolution methods result in up to ten‐fold improvement in resolution by determining the positions of fluorescent molecules with sub‐pixel accuracy. This process critically depends on controlled emission at the level of individual fluorophores so that fluorescence is non‐overlapping, allowing for accurate centroid determination of diffraction‐limited spots by Gaussian fitting of the pixel intensities. The intrinsic photoswitching behavior of many fluorophores provides a convenient way to achieve emitter isolation. Here, we describe methods for label preparation and staining of cellular structures to obtain high‐quality images using localization super resolution. We also compare labeling strategies and dye characteristics relevant to all localization‐based techniques, such as STORM and PALM. Curr. Protoc. Cytom . 63:2.20.1‐2.20.11. © 2013 by John Wiley & Sons, Inc.